PENGARUH SECARA LANGSUNG PENGETAHUAN DAN KECERDASAN EMOSIONAL TERHADAP MANAJEMEN NYERI DI INSTALASI GAWAT DARURAT - Arief Wahyudi Jadmiko (Lembaga Riset Pengabdian Masyarakat dan Publikasi Ilmiah Institut Teknologi Bhakti Putra Bangsa Indonesia, 2017)
Achievement of pain management in the ED is less than optimal. Pain is the most common cause with the percentage as much as 78% -86% of patients come into the ED. Achievement of pain management is determined by internal and external factors. Internal factors capable of empowering the external factors that can support the individual in the service. The purpose of this study was to determine the effect of direct knowledge and emotional intelligence to pain management. This research was conducted in the ED Hospital Dr. Moewardi Surakarta. This research is a quantitative analytical observational cross-sectional design. The study was conducted in June 2014. The samples were 30 nurses. Data analysis using path analysis (path analysis). The collection of data obtained through questionnaires and observation sheets. The research results show that knowledge (⍴ = 0.451, ß = 0.146) and emotional intelligence (⍴ = 0.354, ß = 0.149) does not directly affect pain management. Management of pain in the ED was not directly influenced by the knowledge and emotional intelligence nurse. Increased internal factors can be optimized with formal and informal methods and modify the external factors such as by creating a comfortable environment.